Contes des provinces, edited with exercises and vocabulary by Suzanne Roth. - Morley, Suzanne Roth, editor. (Tufts University. Tisch Library., 2020)
1 online resource (312 pages)frontispiece, illustrations, map.; Tisch In-House Digitization 2019-12-18